Comparison of healthfulness of conventional meats and edible insects in Sub-Saharan Africa using three nutrient profiling models - Johnson Weru; Peter Chege; Anthony Wanjoya; John Kinyuru (Bulletin of the National Research Centre, 2022)
Abstract Background Meat and meat products have been blamed for a myriad of problems facing human kind like lifestyle illnesses, environmental degradation, and climate change. Edible insects have been suggested as the suitable alternatives to conventional meats in order to ameliorate these drawbacks. Healthfulness is the ability for a given food to impart health benefits to the consumer. Evidence is however scanty on the healthfulness of both the meats and edible insects in order to have grounds for replacing meats with insects in the diet. This study aimed to comparatively evaluate the healthfulness of meats and edible insects in Sub-Saharan Africa using modern nutrient profiling models. Materials and methods Nutritional data for meats and edible insects were obtained from Food Composition Tables (FCTs) and a systematic review, respectively. The data was applied to three nutrient profiling models: the WXYfm (Ofcom) model that was designed to regulate advertising of foods to children, the RRR (Ratio of Recommended to Restricted) model that assesses the ratio of positive to negative nutrients in foods, and the GDA (Guideline Daily Amounts) model which has been used to regulate health claims on foods. Tukey's Studentized Range (HSD) Test (The SAS System) was used to check for significance in differences of healthfulness using mean scores. Results The WXYfm model classified all foods as healthful, and Nasutitermes spp. was significantly more healthful than duck (P = 0.05). The RRR classified all foods as healthful, and Nasutitermes spp. was significantly more healthful than all other foods except Macrotermes bellicosus and tilapia (P = 0.05). Duck (for women and men) and pork (for women), were classified as unhealthful by the GDA scoring system, and duck was significantly less healthful than all other foods (P < 0.0001), except for pork and mutton. Conclusion Edible insects are promising alternatives to conventional meats, but the choice should be on a species-to-species basis. This would be significant in broadening the choice of protein sources to cater for an ever-increasing world population.